2021
DOI: 10.1016/j.jhsg.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Patient Resilience and Catastrophizing on Carpal Tunnel Surgical Outcomes

Abstract: Purpose: Outcomes following carpal tunnel release (CTR) are generally favorable. When patient satisfaction or symptom resolution is not as expected, understanding what factors contribute to that outcome could allow for strategies targeted at improving results. Our purpose was to determine if measurable mental health factors, specifically resilience and pain catastrophization, correlate with patients' postoperative outcomes following CTR. Methods: A prospective cohort study was performed. Ninety-four patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…17 Similarly, resilience did not correlate with 3 or 6-month Boston Carpal Tunnel Questionnaire scores after carpal tunnel release. 18 In contrast to the study by Drayer et al, Chavez et al 19 found that in patients who underwent arthroscopic knee surgery, resilience did not correlate with postoperative pain and functional scores at 3 and 6-months. Similarly, we found that preoperative resilience did not correlate with the overall ASES score.…”
Section: Discussionmentioning
confidence: 80%
“…17 Similarly, resilience did not correlate with 3 or 6-month Boston Carpal Tunnel Questionnaire scores after carpal tunnel release. 18 In contrast to the study by Drayer et al, Chavez et al 19 found that in patients who underwent arthroscopic knee surgery, resilience did not correlate with postoperative pain and functional scores at 3 and 6-months. Similarly, we found that preoperative resilience did not correlate with the overall ASES score.…”
Section: Discussionmentioning
confidence: 80%
“…It can provide valuable information on patient resilience for health outcomes. 16,17 The primary aim of this study was to compare physician-and patient-predicted pain tolerance with patientreported pain during injection. Additionally, we aimed to study the relationship between predicted pain tolerance, resilience, pain interference, predicted pain of injection, and pain before injection.…”
Section: Original Articlementioning
confidence: 99%
“…Positive psychology factors include satisfaction with life, gratitude, coping through humor, resilience, mindfulness, and optimism [14]. Resilience, defined as the ability to bounce back from stress or injury, is a specific aspect of positive psychology that has been investigated across multiple areas within orthopedic surgery including total joint arthroplasty, anterior cruciate ligament reconstruction, spine surgery, foot and ankle surgery, and upper extremity surgery, with varying conclusions regarding the association between preoperative resilience and postoperative outcomes [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%